Development of a Dimming and Color Automation System Based on a Microcontroller-Based Dynamic Lighting Scheme - Salehuddin, Muhammad; Bagus Adli Pangestu; Cindy Cornelia; Danial Irfachsyad (ULTIMA Computing, 2025)
Office buildings in urban areas are most likely situated and clustered close to one another, which can impede the penetration of natural sunlight. In contrast, artificial lighting maintains constant intensity and color throughout the day. This paper proposes a strategy to address these limitations by incorporating dynamic lighting systems that automatically adjust the light intensity and color. At this development stage, an IoT-based microcontroller device is deployed. The data collected will be processed and displayed on a web page, providing a monitoring tool for light intensity in the work area. This system's dimming and color adjustment features will be tailored to dynamic lighting characteristics. By conducting laboratory-scale trials using the system design that has been made, it is estimated that 1 lamp can save 17% of electric power compared to if the lamp is lit at maximum conditions continuously.